2011
DOI: 10.1504/ijta.2011.043712
|View full text |Cite
|
Sign up to set email alerts
|

The discourse of risk in horror movies post 9/11: hospitality and hostility in perspective

Abstract: Risk perception has been a newer field of research for tourism scholars. The purpose of this paper is to add to this growing literature by examining how some horror movies play upon the discourses of risk, ethnocentrism, hospitality, and radicalised otherness as a part of their plot lines. In doing so, the authors discuss the literature on risk perception, the role of hospitality in risk perception, and the value of visual and content analysis of movies. Then, four horror movies are presented that include a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 46 publications
0
12
0
5
Order By: Relevance
“…Luego del 11/9 parece ser que la hostilidad se encuentra previamente asociada a la nacionalidad del extranjero, y no a sus actos. En este sentido, los americanos y británicos son más codiciados por los grupos terroristas que otras nacionalidades como argentinos o brasileros (Korstanje & Olsen, 2011). Cualquiera sea el caso, aún se necesita de mucha teoría para comprender la compleja pero persistente relación entre el turista y el terrorista.…”
Section: Fuente: Afp Christofer Simon 2014unclassified
“…Luego del 11/9 parece ser que la hostilidad se encuentra previamente asociada a la nacionalidad del extranjero, y no a sus actos. En este sentido, los americanos y británicos son más codiciados por los grupos terroristas que otras nacionalidades como argentinos o brasileros (Korstanje & Olsen, 2011). Cualquiera sea el caso, aún se necesita de mucha teoría para comprender la compleja pero persistente relación entre el turista y el terrorista.…”
Section: Fuente: Afp Christofer Simon 2014unclassified
“…In tourism and hospitality fields, risk-directed research has been adopted post 9/11 (the attacks that shocked the world against World Trade Centre and other American targets) (Faulkner, 2001;Ritchie, 2004). Although, experts as Roehl and Fesenmaier (1992) have conducted, years earlier, innovative investigation in the matter of risk and the perception of international destinations, an exploding interest in risk as scientific object of study arose (Korstanje & Olsen, 2011). In next section we will discuss the approaches and limitation of risk-perception in tourism studies.…”
Section: Globalizing Riskmentioning
confidence: 99%
“…In earlier studies, Olsen (2011) &Tarlow (2012) examined in detail the synopsis of some horror films which are a part of the horror genre in US. The specialists found that one of the most troubling aspects these films evidence is fear of strangers.…”
Section: Breaking the Rules Of Hospitalitymentioning
confidence: 99%